Pemidanaan Bagi Pelaku Tindak Pidana Pencabulan Dalam Perspektif Kitab Undang-Undang Hukum Pidana Analisis Putusan Nomor 833/Pid/B/2018/PN.JKT.Sel - Lisannul Abror, Farahdiba Bagiawan; Burhanudin; Helmi, Muhammad Ishar (JOURNAL of LEGAL RESEARCH, 2025)
This study analyzes the application of law in the sentencing of perpetrators of sexual harassment and the judicial considerations in deciding such cases, particularly when the criminal sanctions imposed are inconsistent with the prevailing legal provisions. The research aims to understand the implementation of criminal law in punishing offenders and the reasoning of judges in adjudicating sexual harassment cases, with specific reference to the South Jakarta District Court Decision No. 833/Pid/B/2018/PN.JKT.Sel. The study adopts both the case approach and the statute approach, employing a normative legal research method that examines the Indonesian Criminal Code (KUHP) and the relevant court decision as primary sources of analysis. The findings reveal that in the referenced case, the public prosecutor formulated an alternative indictment under Article 290(1) or Article 281(2) of the Criminal Code. The panel of judges ultimately applied Article 281(2) and sentenced the defendant to ten months of imprisonment. The judgment was based on three primary considerations: the testimony of witnesses, the visum et repertum (medical report), and the defendant’s own statement during the trial.